Kultura studencka - próba definicyjnego uporządkowania kategorii = Student culture: an attempt at definitional clarification of the category - Rej, Jakub (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article attempts to provide definitional clarification of the conceptual category: student culture. Based on an analysis of academic culture, the article discusses various definitional approaches to student culture. The foundational theoretical model employed in this study is Schnie`s model of organisational culture.
Keywords: kultura akademicka; kultura studencka; model kultury organizacyjnej Scheina; academic culture; student culture; Schnie`s model of organisational culture